The interaction networks of small rubber particle proteins in the latex of Taraxacum koksaghyz reveal diverse functions in stress responses and secondary metabolism - Wolters, Silva Melissa; Laibach, Natalie; Riekötter, Jenny; Roelfs, Kai-Uwe; Müller, Boje; Eirich, Jürgen; Twyman, Richard M.; Finkemeier, Iris; Prüfer, Dirk; Schulze Gronover, Christian (Frontiers in Plant Science, 2024)
The Russian dandelion (Taraxacum koksaghyz) is a promising source of natural rubber (NR). The synthesis of NR takes place on the surface of organelles known as rubber particles, which are found in latex – the cytoplasm of specialized cells known as laticifers. As well as the enzymes directly responsible for NR synthesis, the rubber particles also contain small rubber particle proteins (SRPPs), the most abundant of which are SRPP3–5. These three proteins support NR synthesis by maintaining rubber particle stability. However, we identified 14 SRPP-like sequences in the T. koksaghyz genome, including one apparent pseudogene, 10 paralogs arranged as an inverted repeat in a cluster with TkSRPP3/4/5, and one separate gene (TkSRPP6). The sequence diversity and different expression profiles indicated distinct functions, so we investigated the functions of TkSRPP3/4/5 by using affinity enrichment mass spectrometry to seek their interaction partners in latex. These experiments suggested TkSRPP4 is a promiscuous hub protein that binds many partners from different compartments, whereas TkSRPPs 3 and 5 have more focused interactomes. TkSRPP4 appears to play a special role in the endoplasmic reticulum, interacting with lipid-modifying enzymes that may facilitate rubber particle formation. TkSRPP5 appears to be involved in GTPase-dependent signaling and TkSRPP3 may act as part of a kinase signaling cascade, with roles in stress tolerance. Two interactors shared by TkSRPP3/4/5 (TkSRPP6 and TkUGT80B1) were chosen for independent validation and detailed characterization. TkUGT80B1 triterpenoid glycosylating activity provided first evidence for triterpenoid saponin synthesis in T. koksaghyz latex and its protein interactors TkSRPP3 and TkSRPP5 might be linked to this process. Our data contribute to the functional differentiation between TkSRPP paralogs and demonstrate unexpected interactions that will help to further elucidate the network of proteins linking TkSRPPs, stress responses and NR biosynthesis within the cellular complexity of latex.